Systematic Review and Meta-Analysis of SERPINE1 4G/5G Insertion/Deletion Variant With Circulating Lipid Levels - Luo, Zhi; Liu, Yang; Li, Hang; Zhou, Yawen; Peng, Yuanyuan; Lin, Xuan; Fang, Ying; Wan, Jing; Wei, Baozhu (Frontiers in Cardiovascular Medicine, 2022)
Background: Recent studies have showed that the 4G/5G insertion/deletion polymorphism of SERPINE1 (rs1799889) is closely linked to acute myocardial infarction (AMI) or coronary artery disease (CAD). However, the potential mechanisms remain unknown, this study aims to clarify the effects of rs1799889 polymorphism on lipid levels, to provide some clues or references for the clarification of possible mechanisms between rs1799889 polymorphism and CAD. Methods and Results: By searching of PubMed and the Cochrane database for studies published before October 31, 2021, 40 studies in a total of 13,117 subjects were included for analyzing. The consistent findings for the effects of the 5G allele of rs1799889 polymorphism on lipid metabolism were the significantly decreased triglycerides (TG) (SMD = -0.12, 95% CI = -0.21--0.03, P = 0.01), total cholesterol (TC) (SMD = -0.12, 95% CI = -0.17--0.06, P < 0.001) and low-density lipoprotein cholesterol (LDL-C) (SMD = -0.13, 95% CI = -0.23--0.03, P = 0.01) levels. Intriguingly, the significant effects of rs1799889 polymorphism on LDL-C and TC levels were primarily observed in Asian populations. However, the significant effect of rs1799889 polymorphism on high-density lipoprotein cholesterol (HDL-C) levels was only observed in female subjects. Conclusions: The rs1799889 polymorphism of SERPINE1 is a protective genetic factor against CAD, the Asian populations with the 5G allele of rs1799889 polymorphism have a reduced CAD risk.